2008
DOI: 10.1002/path.2444
|View full text |Cite
|
Sign up to set email alerts
|

5α‐Dihydrotestosterone (DHT) retards wound closure by inhibiting re‐epithelialization

Abstract: The ongoing search for explanations as to why elderly males heal acute skin wounds more slowly than do their female counterparts (and are more strongly disposed to conditions of chronic ulceration) has identified endogenous oestrogens and androgens as being respectively enhancers and inhibitors of repair. We previously demonstrated that blocking the conversion of testosterone to 5alpha-dihydrotestosterone (DHT) limits its ability to impair healing, suggesting that DHT is a more potent inhibitor of repair than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 28 publications
8
40
2
8
Order By: Relevance
“…For example, MARKO mice exhibited faster wound closure but a similar re-epithelialization rate compared with WT mice, while KARKO and FARKO mice showed delayed and enhanced re-epithelialization, respectively, but a comparable overall wound closure rate The delayed re-epithelialization observed in KARKO mice was not accompanied by a decrease in keratinocyte proliferation, suggesting that keratinocyte AR might promote re-epithelialization by enhancing keratinocyte migration. Such an implication contradicts a recent study by Gilliver et al (10). In that study, DHT treatment inhibited keratinocyte migration in an in vitro migration assay (10), but the effect only became significant at a high dose (100 nM), which is 1-2 orders of magnitude higher than physiological levels of DHT (1-10 nM).…”
Section: Figurecontrasting
confidence: 52%
See 1 more Smart Citation
“…For example, MARKO mice exhibited faster wound closure but a similar re-epithelialization rate compared with WT mice, while KARKO and FARKO mice showed delayed and enhanced re-epithelialization, respectively, but a comparable overall wound closure rate The delayed re-epithelialization observed in KARKO mice was not accompanied by a decrease in keratinocyte proliferation, suggesting that keratinocyte AR might promote re-epithelialization by enhancing keratinocyte migration. Such an implication contradicts a recent study by Gilliver et al (10). In that study, DHT treatment inhibited keratinocyte migration in an in vitro migration assay (10), but the effect only became significant at a high dose (100 nM), which is 1-2 orders of magnitude higher than physiological levels of DHT (1-10 nM).…”
Section: Figurecontrasting
confidence: 52%
“…Earlier studies by Ashcroft and colleagues, using surgical or chemical castration, have found that androgens were able to inhibit cutaneous wound healing, possibly by modulating inflammatory responses, matrix deposition, and keratinocyte function (1,(8)(9)(10). However, the in vivo role of androgens/AR signals in different cell types involved in the wound-healing process remains unclear.…”
Section: Introductionmentioning
confidence: 94%
“…34 This hypothesis is supported by in vitro and in vivo studies to show that α-dihydrotestosterone inhibits wound closure by inhibiting re-epithelialisation. 35 Wound healing impairment Although many extrinsic and intrinsic factors influence surgical outcomes in hypospadias repair, wound healing Key points ■ Hypospadias failure is any repair that leads to complications or causes patient dissatisfaction; the latter is very subjective and difficult to assess ■ Surgeon expertise, interposition of barrier layers between the urethroplasty and the skin, and urinary drainage are the most important factors for preventing hypospadias failure ■ The most common complications associated with hypospadias failure include residual curvature, fistula formation, urethral breakdown, meatal stenosis, and urethral stricture ■ Residual curvature can be addressed by dorsal shortening of the penis; however, urethral substitution should be performed if curvature is caused by a contraction of the ventral neourethra ■ Reurethroplasty technique should be selected according to residual curvature secondary to contracture of the neourethra, quality of the residual urethral plate, and suitability of genital skin for elevating flaps ■ Urethral dilatation and direct vision internal urethrotomy are much less effective than reurethroplasty for treating urethral strictures after hypospadias repair is probably the most important surgeon-independent factor. Wound-healing processes are strongly influenced by hormones, and sex steroids have contrasting roles in the regulation of cutaneous repair processes.…”
Section: Hormonal Stimulationmentioning
confidence: 99%
“…18 The influence of 17␤-estradiol at three concentrations (1, 100, and 1000 nmol/L) on cell migration was evaluated.…”
Section: Keratinocyte Migration Assaymentioning
confidence: 99%